ANALISA PENGARUH MIND MAPPING UNTUK MENUMBUHKAN KEMAMPUAN BERPIKIR KRITIS PADA ANAK SEKOLAH DASAR - Christiana Switaningsih; Dini Rakhmawati; Arri Handayani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The phenomenon of low critical thinking skills of students in basic education with conventional learning models. This study aims to see how far the influence of mind mapping to foster critical thinking skills in elementary school students using the literature review method. This literature study was conducted by analyzing several research articles from 2019 to 2023. Data obtained from Google Schoolar with keywords critical thinking, mind mapping, and elementary school children. The results of this literature obtained 5 articles that fit the criteria of inclusion and exclusion. The results of this literature study show an increase in critical thinking skills of elementary school students using the mind mapping learning model. This is evidenced by analyzing 5 articles that show an average percentage increase in results. Thus, the application of the mind mapping learning model is very helpful for students in improving critical thinking skills and the completeness of learning outcomes in elementary schools.